2004
DOI: 10.1158/0008-5472.can-03-2837
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of 3-Ingenyl Angelate

Abstract: Options for skin cancer treatment currently include surgery, radiotherapy, topical chemotherapy, cryosurgery, curettage, and electrodessication. Although effective, surgery is costly and unsuitable for certain patients. Radiotherapy can leave a poor cosmetic effect, and current chemotherapy is limited by low cure rates and extended treatment schedules. Here, we describe the preclinical activity of a novel topical chemotherapeutic agent for the treatment of skin cancer, 3-ingenyl angelate (PEP005), a hydrophobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
145
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(154 citation statements)
references
References 44 publications
5
145
1
3
Order By: Relevance
“…In previously published studies, PEP005 displayed antiproliferative effects in several human cancer cell lines (Gillespie et al, 2004;Ogbourne et al, 2004;Hampson et al, 2005;Cozzi et al, 2006). Studies that evaluated the activity of PEP005 as a topical agent for human and mouse xenografts have shown that the predominant mechanism of cell death is necrosis (Ogbourne et al, 2004) and in some melanoma cell lines apoptosis was observed (Gillespie et al, 2004). The capacity of PEP005 to induce apoptosis was further confirmed using leukaemia cancer cells (Hampson et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In previously published studies, PEP005 displayed antiproliferative effects in several human cancer cell lines (Gillespie et al, 2004;Ogbourne et al, 2004;Hampson et al, 2005;Cozzi et al, 2006). Studies that evaluated the activity of PEP005 as a topical agent for human and mouse xenografts have shown that the predominant mechanism of cell death is necrosis (Ogbourne et al, 2004) and in some melanoma cell lines apoptosis was observed (Gillespie et al, 2004). The capacity of PEP005 to induce apoptosis was further confirmed using leukaemia cancer cells (Hampson et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
“…In leukaemia cells, resistance to PEP005 was associated with the failure to express PKCd. In solid tumours, PEP005 was shown to induce necrosis in human melanoma, cervical cancer, and prostate xenografts (Ogbourne et al, 2004).…”
mentioning
confidence: 99%
“…Whether the anti proliferative activity observed for the Zyzyphus Jujube extract is due to the induction of apoptosis was examined in our study. Results of DNA fragmentation showed Zyzyphus Jujube has the ability to induce apoptosis in Jurkat cells (Ogbourne et al 2004). Previously, the anti proliferative activity in gastric tumors in nude mice has been demonstrated for CKBM, a mixture of natural herbs containing Zyzyphus Jujube.…”
Section: Discussionmentioning
confidence: 96%
“…Apoptosis is a highly regulated process that occurs as part of differentiation, proliferation and growth of normal and malignant cells and plays a critical role in tumor initiation, progression, as well as in cancer therapy (Kim et al 2002;Ogbourne et al 2004). Whether the anti proliferative activity observed for the Zyzyphus Jujube extract is due to the induction of apoptosis was examined in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, a number of compounds targeting protein kinase C are currently at different stages of drug development. Examples include LY333531, being evaluated for diabetic retinopathy and anti-angiogenesis (1, 2), prostratin and dPP, being evaluated for AIDS chemotherapy (3,4), and bryostatin 1 and ingenol 3-angelate, being evaluated as cancer chemotherapeutic agents (5)(6)(7).…”
mentioning
confidence: 99%